Physical Model and Bases of Mathematical Modelling of Above-Surface Gasification of Coal; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Arukov R. N. (2016, 2016)
Title screen